Concentração bancária no Brasil: trajetórias e conversão de capitais dos conselheiros administrativos dos cinco maiores bancos - Vila, Marcio Luis (2020)
This research analyzed banking concentration in Brazil after the Plano Real implementation in 1994, and how the five largest banks (financial groups) increased their market share, after the insertion of government programs for the privatization of state banks and the restructuring of financial institutions. The trajectory and the capital of board members fromthe five major banks were also evaluated. The objective of research was to analyze longitudinally the banking concentration in Brazil from the Plano Real, to identify the professional trajectory of the directors and what capitals were invested during their careers, as well as the conversion of these capitals, according to Bourdieu's theory. This study used qualitative methodological approach, the research took place through documents analysis, historical and descriptive, with use of prosopography as an investigation technique. Were used data from the five largest financial groups operating in the Brazilian territory, namely: Banco do Brasil, Caixa Econômica Federal, Itaú-Unibanco, Bradesco and Santander, as well as the members of respective Boards of Directors. The main results of the research show the three private banks in the study have expanded their leadership positions through mergers and acquisitions, while state-owned banks, having the government seal, managed to keep up with the largest private banks. The Plano Real and the 2008 Financial Crisis were the biggest tests the banks faced, and as a result we saw an increase in equity and net income surpassing historical series. Regarding the trajectory of the Board members, three types were identified, namely: “De carreira”, a trajectory in which the professionals worked for a lifetime in the institution; “Familiar”, are the professional heirs of the founding families; and “De Mercado”, where most professionals located, are specialists / technicians with long experience in other institutions.